Situational Leadership, Organizational Support, and Self-Efficacy as Predictors of Teacher Work Motivation in Indonesian Junior High Schools - Muhammad Triyoso; Aslamiah Aslamiah; Sulistiyana Sulistiyana (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines the direct and indirect effects of situational leadership and organizational support on junior high school teachers’ work motivation, with self-efficacy as a mediating variable. A quantitative correlational design with path analysis was employed. The sample comprised 128 teachers randomly selected from a population of 203 teachers in Kotabaru Regency, Indonesia. Data were collected using validated Likert-scale questionnaires (Cronbach’s α > 0.96 for all variables). Path analysis revealed that situational leadership (β = 0.315, p = 0.008) and organizational support (β = 0.377, p < 0.001) have significant direct effects on self-efficacy, which in turn significantly predicts work motivation (β = 0.376, p = 0.010). Self-efficacy partially mediates the relationships between both situational leadership and organizational support on work motivation. The model explained substantial variance in self-efficacy (R² = 0.68) and work motivation (R² = 0.71). These findings confirm that teacher work motivation is enhanced by adaptive school leadership, supportive organizational environments, and strengthened teacher self-belief. Practical implications include developing principal training programs in situational leadership and creating organizational support systems that foster teacher self-efficacy. Limitations include the cross-sectional design and single geographic setting; future research should employ longitudinal designs across diverse educational contexts.